0.05 room flat - Ng, Si Ying (2016)
Housing is a type of security in the lives of Singaporeans and also a form of investment in which people seek comfort. However, in our world today, society is constantly confronted with change: natural and man-made disasters are occurring more often, in addition to conflicts and wars. How long will people be safe in their homes? Statistics has shown that the issue of global displacement is a high possibility in our future times. Hence, this project seeks to challenge the certainty society has in the safety of Singapore, within a speculative context of a possibly displaced future Singapore. It explores the idea of providing a bare minimum space needed for survival should displacement happen. This is done via the design of an alternative portable home for one called the 0.05 Room Flat.